Analysis of Learning Obstacles for High School Students in Linear Program Materials - Yosi Cahyaningtyas Fitri; Al Jupri (Universitas Negeri Makassar, 2026)
This study analyzes the learning obstacles encountered by senior high school students in linear programming. A qualitative method with a phenomenological approach and didactical design research was employed. The participants comprised 28 eleventh-grade students from a public high school in Kampar, Indonesia, all of whom had previously studied two-variable linear inequality systems. Data collection involved written tests, interviews, and document analysis, and the data were analyzed using data reduction, data display, and conclusion drawing techniques. The results reveal three types of learning obstacles: ontogenetic, epistemological, and didactic. Ontogenetic obstacles include low motivation, insufficient readiness, and limited mastery of prerequisite concepts. Epistemological obstacles are evident in students’ misconceptions when modeling problems and identifying solution regions. Didactic obstacles result from instructional practices that prioritize procedural steps over conceptual understanding. These obstacles interact and collectively contribute to students’ difficulties in solving linear programming problems. The findings underscore the importance of analyzing learning obstacles to inform instructional approaches that foster meaningful learning and enhance students’ understanding of linear programming concepts.